The Cherry collection of Deg Hit'an (Ingalik) material culture / Fieldiana, Anthropology, new series, no.27 - VanStone, James W.; Field Museum of Natural History. (Chicago, Ill. : Field Museum of Natural History, 1996)
The collections of the Field Museum of Natural History contain 128 ethnographic objects collected among the Deg Hit'an (Ingalik) Indians at Anvik, Alaska, in 1890-1892. Marcus O. Cherry assembled the collection for the World's Columbian Exposition in 1893. The artifacts in this collection are described and illustrated. For comparative purposes, information is included from a previous study of Deg Hit'an material culture by Cornelius Osgood (1940) and from other relevant sources. Includes bibliographical references (p. 21-23). The collections of the Field Museum of Natural History contain 128 ethnographic objects collected among the Deg Hit'an (Ingalik) Indians at Anvik, Alaska, in 1890-1892. Marcus O. Cherry assembled the collection for the World's Columbian Exposition in 1893. The artifacts in this collection are described and illustrated. For comparative purposes, information is included from a previous study of Deg Hit'an material culture by Cornelius Osgood (1940) and from other relevant sources. Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).